Assumptions about Frailty and the Tenacity of Ageism among Care Professionals - Kane, Michael N. (Journal of pastoral care & counseling, 2018)
Health, mental health, and pastoral care professionals encourage individuals to care for themselves in order to age successfully. Younger persons who live with long-term physical or mental health challenges are perceived as disabled or health-challenged. When older persons possess long-term physical or psychiatric challenges the older individual is perceived as frail or with deficits. Implications for clinical and pastoral care are considered as a result of perceptions of frailty in an ageist culture.